Efek Pemberian Kulit Buah Coklat Fermentasi Terhadap Pertumbuhan Kambing Kacang - Harapin Hafid; N Nuraini; Asma Bio Kimestri (Fapetrik-UMPAR, 2021)
Utilization of fresh cocoa fruit skin and the results of fermentation as green feed a goat was conducted to determine the effect of fermentation of the cocoa fruit skin against weight gain local goats. The study was conducted for 3 months using 8 goats aged 4-5 months who were randomly assigned to two treatment groups. The treatments were 85% field grass added 15% fresh cacao pods (F1) and 85% field grass added 15% fermented cocoa pod husks (F2). Each treatment consisted of four groups as replicates. The results showed that both treatments of giving fresh and fermented cocoa pods had the same effect on palatability and weight gain of goats. Feeding fresh and fermented cacao pods can still be used as a supplementation material for local goats.